INTEGRITAS SISWA DI PAPUA BARAT - Asnandar Abubakar (EDUCANDUM, 2018)
This study aims to find out how much the integrity of students in the aspects ofhonesty, responsibility, tolerance, and love of homeland at the level ofsecondary education and its supporting factors. The study was conducted inseven districts/cities of West Papua Province in senior high schools andmadrasah aliyah. This is a qualitative research by distributing questionnairesas an instrument for collecting data on 10 students class XI in eachschool/madrasah. Analysis of data that has been tabulated is done using theSPSS application. The results showed that students' integrity was at a highlevel in all aspects; honesty 78%, responsibility 69%, tolerance 84%, andlove of homeland 90%. Likewis the supporting factors influence thestrengthening of integrity because it includes religious nuances and values.The results of the analysis also show that the environment of schools, familiesand residences correlates with aspects of honesty, responsibility, and love ofthe homeland. Aspects of tolerance are less correlated with the threesupporting environmental aspects. Factors in the availability of religiousteachers in schools / madrasas are also important aspects for strengtheningstudent integrity. In general, the integrity of students in West Papua Provinceis at a high level of 80%.